New dilemmas in young people’s mobile transitions during the Covid-19 pandemic - Cairns, D.; Clemente, M. (Transitions on hold?: How the Covid-19 pandemic affected young people’s transitions to autonomy, 2023)
The impact of the Covid-19 pandemic on youth transitions is potentially huge, due to the severity of the public health emergency and its prolonged duration. At the time of writing, December 2021, a fifth wave of infections has started in western Europe, accelerated by the rapid spread of the Omicron variant, taking us into a third successive year, with no end as yet in sight. With thousands of people dead, millions more infected, some repeatedly, and the social and economic positions of practically everyone disrupted in some respect, we can say without fear of contradiction that young people will be making a transition to a reality different from previous generations, characterised by changes that traverse socio- and geo-demographic boundaries. This is not to mention challenges that pre-date the pandemic, and will no doubt outlast it, including the climate emergency and rising geo-political tensions in central and eastern Europe, all of which complicate the process of growing up and becoming independent.